2020
DOI: 10.3151/jact.18.116
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Protection Performance of an Internal Blending Organic Corrosion Inhibitor for Carbon Steel in Chloride Contaminated Simulated Concrete Pore Solution

Abstract: Application of corrosion inhibitors is considered as one of the most economical and effective solutions for the protection of reinforced concrete structures under severe environment. The aim of this paper is to investigate the protection performance and mechanism of an internal blending organic inhibitor for carbon steel in chloride contaminated simulated concrete pore solution. The influences of concentration of inhibitor, chloride content and pH value of the solutions on the protection efficiency were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 61 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…However, the strength for the concrete produced using 30% FA compared to that of corresponding concrete no fly ash had an average shrinkage of 2.4%. This phenomenon was attributed to micro-aggregate filling and the pozzolanic effects of fly ash [ 20 , 21 ]. Nevertheless, a high volume of fly ash incorporation magnified total porosity result in density reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the strength for the concrete produced using 30% FA compared to that of corresponding concrete no fly ash had an average shrinkage of 2.4%. This phenomenon was attributed to micro-aggregate filling and the pozzolanic effects of fly ash [ 20 , 21 ]. Nevertheless, a high volume of fly ash incorporation magnified total porosity result in density reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Concrete durability was adversely influenced by many physical effects, including wear of frictional surface, cracking on account of pore solution crystallization, faced with the atrocious circumstance in temperature (frost or heat action, for instance), and detrimental chemical effects, including lixiviating of the cement paste because of acidic solutions [ 18 ] and expansive substances by sulfate attack [ 19 , 20 ]. In comparison, corrosion of reinforcement by the chlorine ion in concrete structures [ 21 ] was one of the biggest and the most serious factors in saline-alkali soil, areas covered with deicing salts, and coastal environments. Under the combination of chlorine corrosion and the freeze-thaw cycle, a more complex physical and chemical process occurs where high free chloride ions would partially destroy the passive film of reinforcement, and then the iron matrix would be exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is currently the most used building material 1–7 . However, under the effect of freezing and thawing, chloride penetration, sulfate attack, etc., the reinforced concrete structure often cannot reach the designed service life 8–13 . In order to maintain the performance of the reinforced concrete structure, it needs to be repaired and strengthened.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of reinforcements in engineering applications is regarded as one of the most key elements that reduces the service life of reinforced concrete (RC) structures. [1][2][3][4] It has been reported that 55% of the deterioration and degradation of RC structures is induced by the corrosion of steel rebars. 5 One of the major causes of corrosion of steel is ascribed to chloride ingress, especially due to the exposure of RC structures to marine or coastal environments.…”
Section: Introductionmentioning
confidence: 99%